2020
DOI: 10.3390/molecules25102288
|View full text |Cite
|
Sign up to set email alerts
|

Clerodane Diterpenoids from Callicarpa hypoleucophylla and Their Anti-Inflammatory Activity

Abstract: Plants of the genus Callicarpa are known to possess several medicinal effects. The constituents of the Taiwan endemic plant Callicarpa hypoleucophylla have never been studied. Therefore, C. hypoleucophylla was selected for our phytochemical investigation. Two new clerodane-type diterpenoids, named callihypolins A (1) and B (2), along with seven known compounds were isolated from the leaves and twigs of the Lamiaceae plant C. hypoleucophylla and then characterized. The structures of compounds 1 and 2 were eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous research showed that labdane and clerodane diterpenoids exhibit varying levels of anti-inflammatory activity. Thus, sufficient novel compounds ( 1–4 , 6–12 , 15–18 , and 21 ) were tested for their anti-inflammatory activities against LPS-induced NO production in RAW264.7 murine macrophages (Table and Figure S224). In addition, these compounds were also tested for their cytotoxic activities against RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research showed that labdane and clerodane diterpenoids exhibit varying levels of anti-inflammatory activity. Thus, sufficient novel compounds ( 1–4 , 6–12 , 15–18 , and 21 ) were tested for their anti-inflammatory activities against LPS-induced NO production in RAW264.7 murine macrophages (Table and Figure S224). In addition, these compounds were also tested for their cytotoxic activities against RAW264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Hautriwaic acid ( 196 ) from Dodonaea viscosa leaves, used for rheumatism, exhibited anti-inflammatory activity in a mouse ear edema model [ 66 ]. Clerodane compounds 164 – 175 from Callicarpa hypoleucophylla suppress superoxide anion generation and elastase release, inhibiting the function of human neutrophils [ 61 ]. Trans -crotonin inhibits dextran- and histamine-induced oedema [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reveal that the clerodane diterpenoids exhibited anti-inflammatory activity. ,,, Therefore, the anti-NLRP3 inflammasome effects of compounds 1 and 2 were evaluated . First, mouse macrophage J774A.1 cells were stimulated by nigericin with the treatment of compounds 1 and 2 .…”
mentioning
confidence: 99%